An investigation of the conditions leading to strip adhesion in industrial steel coils - Wakaba, Lulama Velile (University of the Free State, 2001)
During the production of steel strip, a significant amount of work hardening takes place when the steel is rolled into thin strips, which are stored in a coiled form. These steel coils are batch annealed in order to reduce the hardness and restore formability, before further processing takes place. The development of diffusion welds between spirals of steel coils, during batch annealing, is of particular interest because it prevents the coils from being unwound for further use. This problem is often referred to as strip adhesion or stickering. In order for strip adhesion to develop, it is essential for some coil spirals to be in contact, while the inter-diffusion between spirals takes place. Furthermore, high temperatures also aid in the diffusion process. It is therefore useful to study the temperature and resulting thermal stress distributions in the coil, during batch annealing. The temperature distribution allows for the calculation of thermal stress, which is the driving force for establishing contact between spirals, and in addition to this, the temperature distribution also provides some clues regarding the likelihood of inter-diffusion. In this study, models of temperature and stress are presented. A two-dimensional finite difference model for temperature is presented and confirmed by an analytical solution of the same problem. Analysis of a three-dimensional temperature model in the third chapter shows that, as far as heat transfer is concerned, a cylindrical coil can be well approximated by a solid cylinder with a concentric hole. All the temperature modeling was done for the interior of a coil. Further discussion in later chapters shows that a cylindrical coil can also be treated as a solid cylinder for thermal stress modeling. A long cylinder stress model in the fifth chapter provides some useful insight, as far as strip adhesion is concerned, even though it is a one-dimensional model that does not consider the effect of axial heat transfer. The radial compressive stress during the cooling stage of the batch annealing process was identified as a paramount ingredient to strip adhesion. The thermal stress calculations are later extended to include a linear cooling temperature ramp and these results are arguably the most important findings of this study. According to these results, when the a cylinder is cooled in such a way that the outer edge lags behind the cooling of the inner edge, by a few hours, the compressive radial stress is greatly reduced. Consequently, the contact pressure between spirals at the most critical stage of batch annealing (where strip adhesion occurs) is decreased and the chance of strip adhesion developing is reduced.
Dissertation (M.Sc. (Physics))--University of the Free State, 2001
Keywords: Adhesion; Thermal stresses; Heat -- Transmission